Impact of Self-Registration Booth on Service Quality at Dr. OEN Hospital Solo - Pungki Sanastri; Edy Susena (Universitas Muhammadiyah Malang, 2025)
The implementation of Self-Registration Booth (SRB) aims to enhance healthcare service quality by providing a streamlined, efficient, and user-friendly registration process. This study evaluates the impact of SRB on healthcare service quality at Dr. OEN Hospital Solo using the SERVQUAL model, focusing on five dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. A descriptive-quantitative approach was applied, involving 100 outpatient respondents and interviews with five registration staff members. The results indicate an overall satisfaction score of 3.6, with Tangibles scoring the highest (3.8) and Empathy the lowest (3.4). Technical issues such as system errors, BPJS integration problems, and slow response times were identified as significant challenges. Despite improvements in efficiency, the role of registration staff remains crucial, especially in assisting patients unfamiliar with the system. Recommendations include enhancing system reliability, user guidance, and integration with BPJS to improve service quality.